Development of Case Method-Based Learning Tools to Enhance Learning Outcomes in Engineering Physics Course - Erniwati Erniwati; Wa Ode Nirwana Sari Halidun; Kasman Kasman; Abdin Abdin; Muhammad Sirih (Jurnal Pendidikan Fisika Indonesia, 2026)
This study aims to develop a learning tool using the case method in an engineering physics course. The 4D (define, design, develop, disseminate) development model is used as the methodology. The development model is used to determine the feasibility and effectiveness of learning tools in improving the learning outcome. The validation sheet, questionnaire, and written test sheet were used as the data collection techniques. The validation sheet consists of construction and content validation. The questionnaire is used to collect descriptive data on the practical teaching materials test, and the written test sheet consists of a pretest and a post-test, which are used to determine learning outcomes improvement. The validation test results showed that the case-based learning tools in the engineering physics course were categorized as very valid. The practicality of case-based learning tools is evaluated through an analysis of lecturer and student responses. The results showed that the practical case-based learning tools were rated as very practical. Effectiveness can be determined from the N-gain score from the pretest and posttest. The result showed that the N-gain score was in the medium range, indicating improvement in the learning outcome. According to the results above, the development of learning tools using the case method has been declared feasible and effective for application in the engineering physics course.